Maternal opioids age-dependently impair neonatal respiratory control networks - Beyeler, Sarah A.; Naidoo, Robyn; Morrison, Nina R.; McDonald, Emilee A.; Albarrán, David; Huxtable, Adrianne G. (Frontiers in Physiology, 2023)
Infants exposed to opioids in utero are an increasing clinical population and these infants are often diagnosed with Neonatal Abstinence Syndrome (NAS). Infants with NAS have diverse negative health consequences, including respiratory distress. However, many factors contribute to NAS, confounding the ability to understand how maternal opioids directly impact the neonatal respiratory system. Breathing is controlled centrally by respiratory networks in the brainstem and spinal cord, but the impact of maternal opioids on developing perinatal respiratory networks has not been studied. Using progressively more isolated respiratory network circuitry, we tested the hypothesis that maternal opioids directly impair neonatal central respiratory control networks. Fictive respiratory-related motor activity from isolated central respiratory networks was age-dependently impaired in neonates after maternal opioids within more complete respiratory networks (brainstem and spinal cords), but unaffected in more isolated networks (medullary slices containing the preBötzinger Complex). These deficits were due, in part, to lingering opioids within neonatal respiratory control networks immediately after birth and involved lasting impairments to respiratory pattern. Since opioids are routinely given to infants with NAS to curb withdrawal symptoms and our previous work demonstrated acute blunting of opioid-induced respiratory depression in neonatal breathing, we further tested the responses of isolated networks to exogenous opioids. Isolated respiratory control networks also demonstrated age-dependent blunted responses to exogenous opioids that correlated with changes in opioid receptor expression within a primary respiratory rhythm generation region, the preBötzinger Complex. Thus, maternal opioids age-dependently impair neonatal central respiratory control and responses to exogenous opioids, suggesting central respiratory impairments contribute to neonatal breathing destabilization after maternal opioids and likely contribute to respiratory distress in infants with NAS. These studies represent a significant advancement of our understanding of the complex effects of maternal opioids, even late in gestation, contributing to neonatal breathing deficits, necessary first steps in developing novel therapeutics to support breathing in infants with NAS.